PROCEEDINGS XIV CONGRESSO BRASILEIRO DE TRANSPLANTES; XIV CONGRESSO LUSO BRASILEIRO EM TRANSPLANTES; V ENCONTRO MULTI DISCIPLINAR EM TRANSPLANTES AND FÓRUM DE HISTOCOMPATIBILIDADE DA ABH - Associação Brasileira de Transplante de Órgãos, (Brazilian Journal of Transplantation, 2016)
In this issue are presented abstracts of COORDINATION; ETHICS; PEDIATRICS; TISSUE; PSYCHOLOGY; EXPERIMENTAL; NUTRITION; ANESTHESIA AND PHARMACY.